(untitled) (Tempo e Argumento, 2022)
This paper discusses the relation between teaching and research with basic education History teachers in continual teaching education. It aims to point out how the relation between education, teaching and research is transversal to the teaching processes on higher education as well on basic education. The paper presents the research scenery – the Mestrado Profissional em Ensino de História – ProfHistória course (Universidade do Estado da Bahia – UNEB center) and details the research’s context in which this text is based. The scope of this paper is defined based on bibliographical dialogues with authors who discuss the teaching-researching relation, qualitative methodologies, and case studies. The research started in the 2020.1 semester with the newly joined class of ProfHistória – UNEB. It aims to know: how does the class reflect upon the formation, teaching, and research relation? Upon interpreting the research findings, data points to the hurdles teachers face through their professional careers, which raises questions about their own formation. Out concluding remarks take up the question asked at the beginning of the introduction of the text, about how does the class reflect upon the formation, teaching, and research relation, aiming to a teaching practice more involved with the current challenges of basic education.